Comparison of combined intranasal dexmedetomidine and ketamine versus chloral hydrate for pediatric procedural sedation: a randomized controlled trial - Young-Eun Jang; Eun-Young Joo; Jung-Bin Park; Sang-Hwan Ji; Eun-Hee Kim; Ji-Hyun Lee; Hee-Soo Kim; Jin-Tae Kim (Korean Journal of Anesthesiology, 2025)
Background We hypothesized that intranasal combination of dexmedetomidine (2 μg/kg) and ketamine (3 mg/kg) (IN DEXKET) improves the success rate of sedation in pediatric patients compared with chloral hydrate (CH; 50 mg/kg). Methods This prospective, two-center, single-blinded, randomized controlled trial involved 136 pediatric patients (aged < 7 years) requiring procedural sedation. The participants were randomized to receive CH or IN DEXKET via a mucosal atomizer device. The primary outcome was the success rate of sedation (Pediatric Sedation State Scale, scores 1–3) within 15 min. The secondary outcomes included sedation failure at 30 min and overall complications of first-attempt sedation. Results After excluding eight patients, 128 were included (CH = 66, IN DEXKET = 62). IN DEXKET showed a similar sedation success rate (75.8% [47/62] vs. 66.7% [44/66]; P = 0.330) but a lower complication rate (3.2% [2/62] vs. 16.7% [11/66]; P = 0.017) than CH. In the subgroup analysis for patients aged < 1 year, IN DEXKET showed a reduced complication rate than CH (2.6% [1/38] vs. 22.9% [8/35]; P = 0.012). In the subgroup analysis of children aged 1–7 years, IN DEXKET showed a higher sedation success rate within 15 min (79.2% [19/24] vs. 51.6% [16/31]; P = 0.049) and a lower sedation failure after 30 min (0% vs. 29.0% [9/31]; P = 0.003) than CH. Conclusions The intranasal combination of dexmedetomidine (2 μg/kg) and ketamine (3 mg/kg) is a safe and effective alternative to CH (50 mg/kg) for sedation in pediatric patients aged < 7 years.